THE USE OF THINK PAIR SHARE METHOD IN TEACHING ENGLISH TO IMPROVE STUDENTS’ SPEAKING MASTERY AT THE GRADE XI OF SMK NEGERI 1 PADANGSIDIMPUAN - Apriyanti Hasibuan (Universitas Muhammadiyah Tapanuli Selatan, 2016)
This research deals with analysis the use of think pair share method could be improved students’ mastery in speaking English. The sources of data was the grade XI TKJ-1 SMK Negeri 1 Padangsidimpuan, which consisted of six students as the participants.The participants were divided into three groups; the first group (2 student) was the high ability. The second group (2 students) was the middle ability. The third group (2 students) was low ability. This research used qualitative method with descriptive analysis technique. The purpose of this research to know the using of think pair share method to improve students’ speaking mastery at the grade XI of SMK Negeri 1Padangsidimpuan which usefull to make students comfort to express their ideas and enjoy to communicate in English.